การใช้เตาเผาไฟฟ้าแบบขดลวดความต้านทานสำหรับการสังเคราะห์อะลูมิเนียม พิลลาร์มอนต์โมริลโลไนต์ APPLICATION OF AN ELECTRIC RESISTANCE FURNACE FOR SYNTHESIS OF Al-PILLARED MONTMORILLONITE - ชื่นชมนาคจาด ศักดิ์สิทธิ์; สีตะมา นิดา; ทองคำ ดวงรัตน์ (Srinakharinwirot University Journal of Sciences and Technology, 2021)
In this research, a low-cost electric furnace was designed and fabricated by using resistant coils that provided the maximum heating temperature up to 1,200°C. The furnace was made of refractory bricks, ceramic fibers, ceramic rods, resistant coils, and silica boards, a thermocouple was installed inside. The furnace can be used for calcination of aluminum pillared montmorillonite (Al-Mt1 and Al-Mt2). The prepared montmorillonites were characterized by various techniques such as Fourier transform infrared spectroscopy. The results confirmed the presence of pillars because of the decrease in the intensity of OH and Si-O-Si groups. The data from Brunauer Emmett-Teller displayed the specific surface area of Al-Mt1 (217.3625 m2/g) was greater than that of Al-Mt2 (203.2639 m2/g). The N2 adsorption isotherms exhibited Type IV behaviors according to the IUPAC classification. Moreover, alkylamine chloroanthraquinone molecules (L) were added to the Al-Mt1 and Al-Mt2 structures to form AlMt1-L and AlMt2-L, respectively. The prepared materials were used as adsorbent for removal of copper ion (Cu2+) and were characterized by UV-visible spectroscopy. The Cu2+ removal efficiency using AlMt1-L was around 10% higher than that of AlMt2-L. In addition, the quantity of Cu2+ adsorbed (qt) by AlMt1-L was about four times higher than that of AlMt2-L.